Preclinical evaluation of novel tumour vasculature disrupting agents - Prokopiou, Ekatherine M. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
Targeting of tumour vasculature and angiogenesis represents an ideal approach in the design of cancer therapeutics since all types of solid tumours are dependent upon a blood supply for growth and survival. The best known vascular disrupting agents are the tubulin binding agents, which as a result of their effect on microtubule dynamics; cause cell cycle arrest, morphological changes to endothelial cells and subsequent tumour vascular shutdown. Aminopeptidase N (APN) is an exopeptidase which plays a key role in tumour cell invasion, extracellular matrix degradation and tumour metastasis. It is expressed in proliferating endothelial cells undergoing angiogenesis but not in quiescence endothelial cells, as well as in a variety of tumour cells (e.g. PC-3 cells). Thus, APN is an ideal therapeutic target for angiogenesis, invasion and APN-expressing tumours. In our laboratory, single tubulin polymerisation inhibitors, dual-acting hybrids and designed multiple ligands, targeting tubulin polymerisation and APN (using bestatin) were designed, synthesised and evaluated in preliminary protein-based assays. The purpose of the studies described in this doctoral thesis was to extend this work and evaluate test compounds’ anti-vascular, anti-angiogenic and anti-tumour activity in enzyme, cellular, ex vivo and in vivo settings.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin